The spatial evolution and optimization of supply channels for marine products consumed in China. Issue 5 (4th July 2022) - Sun, Yu; Lian, Feng; Guo, Weiyou; Yang, Zhongzhen
ABSTRACT: We introduce quaternary and ternary diagrams to analyze temporal-spatial changes in the supply and demand shares of marine products, respectively. Subsequently, we build a marine product supply selection model to calculate the quantities of marine products furnished by supply channels and estimate the demand for marine products in China's three coastal areas. These are used to demonstrate the supply gap of marine products in China before we optimize and adjust the supply scheme of marine products for China. The results show that China's coastal areas import large volumes of fish, crustaceans and molluscs. In the Bohai Bay Rim, the domestic supply of marine products (except for fish and crustaceans) is greater than imports, while in the Yangtze River Delta and Southern China coastal areas, the domestic supply of all marine products is greater than imports. Domestic channels thus cannot fully satisfy coastal demand for marine products. In order to meet the demand, China should enlarge its imports from Europe and Asia, encourage ocean-going fishing vessels to directly transport all harvests back to China, and strengthen fishing port construction so as to promote the development of China's seafood imports and pelagic fisheries.